Product‐quality failures in international sourcing: effect of institutions - Muralidharan, Etayankara; Wei, William Xiaojun; Zhang, Juan; Bapuji, Hari (My University, 2016)
Increasing globalization has seen the emergence of hybrid products coming from different countries, which are the sourcing bases for multinationals. Such international sourcing decisions of multinational enterprises have been accompanied by concerns on product safety especially underscored by the increasing product failures leading to recalls from global supply chains witnessed in the recent past. While the past research has focussed largely on the consequences of recalls such as damage to the reputation of the firm and stock price erosion, the antecedents of such failures and recalls remain underresearched. We examine international sourcing through a multitheoretic lens to investigate how the unfavorability of institutions of the countries from where products are sourced increases the likelihood of product failures. We propose that international experience of the firm, supplier development initiatives, and the firm’s strategic nature of sourcing all moderate the relationship between institutional constraints and product-quality failures.
Keywords: institutions; product-quality failures; knowledge transfer; monitoring